2019
DOI: 10.1111/cmi.13123
|View full text |Cite
|
Sign up to set email alerts
|

The PHIST protein GEXP02 targets the host cytoskeleton during sexual development of Plasmodium falciparum

Abstract: A hallmark of the biology of Plasmodium falciparum blood stage parasites is their extensive host cell remodelling, facilitated by parasite proteins that are exported into the erythrocyte. Although this area has received extensive attention, only a few exported parasite proteins have been analysed in detail, and much of this remodelling process remains unknown, particularly for gametocyte development. Recent advances to induce high rates of sexual commitment enable the production of large numbers of gametocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…Lastly, gametocytes lacking PfARID also showed dysregulation (both upregulated and downregulated) of a large number of heterochromatin-associated multigene families such as VAR ( 73 ), RIFIN ( 74 ), and PHISTa/b/c ( 75 ), which are known to regulate cytoadherence of infected RBCs, immune escape, and other parasite/host interactions, mainly in the parasites’ asexual blood stages. These gene families are, however, also expressed in gametocytes ( 76 79 ). VAR gene expression encoding PfEMP1 proteins might continue to provide variant antigen expression and immune escape in gametocytes during maturation ( 76 ), and PHIST family proteins are exported during gametocytogenesis ( 77 ) and control infected RBC rigidity ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, gametocytes lacking PfARID also showed dysregulation (both upregulated and downregulated) of a large number of heterochromatin-associated multigene families such as VAR ( 73 ), RIFIN ( 74 ), and PHISTa/b/c ( 75 ), which are known to regulate cytoadherence of infected RBCs, immune escape, and other parasite/host interactions, mainly in the parasites’ asexual blood stages. These gene families are, however, also expressed in gametocytes ( 76 79 ). VAR gene expression encoding PfEMP1 proteins might continue to provide variant antigen expression and immune escape in gametocytes during maturation ( 76 ), and PHIST family proteins are exported during gametocytogenesis ( 77 ) and control infected RBC rigidity ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…These gene families are, however, also expressed in gametocytes ( 76 79 ). VAR gene expression encoding PfEMP1 proteins might continue to provide variant antigen expression and immune escape in gametocytes during maturation ( 76 ), and PHIST family proteins are exported during gametocytogenesis ( 77 ) and control infected RBC rigidity ( 80 ). Host cell deformability and rigidity change late in gametocytogenesis and are possibly critical factors in gametocyte transmission to the mosquito vector ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed significant changes (both increased and decreased) in the transcript abundance of members belonging to multigene heterochromatin-associated families such as P. falciparum VAR , RIFIN , STEVOR , and PHIST in the Pfsrpk1 − parasites. These gene families were reported to be expressed in gametocytes ( 85 89 ). It has been suggested that VAR gene expression may continue to provide variable antigenic expression in gametocytes during maturation inside the human host ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that VAR gene expression may continue to provide variable antigenic expression in gametocytes during maturation inside the human host ( 85 ). Similarly, PHIST family proteins are exported during gametocytogenesis ( 86 ) and control infected RBC rigidity ( 90 ). Host cell deformability and rigidity changes occur late in gametocyte development and are possible crucial factors in gametocyte transmission to the mosquito vector ( 91 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pf3D7_0532400 is a lysine-rich membrane-associated protein that directly associates to infected red blood cell (iRBC) cytoskeletons and enhances cytoadherence to Cd36 4 . Pf3D7_1102500 is a gametocyte export protein and interacts with the cytoskeleton 6 , while Pf3D7_1401600 contains an MEC domain 6 , its function is largely unknown apart from an association with placental malaria 6 affects iRBC membrane rigidity 7 and is upregulated in sexually committed parasites 8 . Recent reports by Rono et al, identified some PHISTb genes to linked to parasite adaptation to local malaria transmission forces.…”
Section: A Clear Justification Describing Why Focusing On These 3 Proteins And/or Regions Should Be Considered As Representative Of the Ementioning
confidence: 99%